Economic Impact of Wind Integration on Primary Frequency Response - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2015)
In order to have a reliable and secure power system, frequency stability should be guaranteed. Primary Frequency Response (PFR) is used to arrest the frequency deviation upon a contingency. The significant penetration of wind generation in power grids has negative effect on the PFR, as the contribution of wind machines to the total system inertia is low and classical wind turbines do not have PFR capabilities. This study uses two metrics of frequency control, ROCOF and frequency Nadir to analyze the cost increase for maintaining adequacy in the presence of wind power. The Nordic 32-A test grid, representing the Swedish grid is used as case study on which the method is applied. © 2015 IEEE.